DIGITAL CULTURE AND THE EDUCATION OF PHYSICAL EDUCATION TEACHERS: A CASE STUDY IN UNIPAMPA - Bianchi, Paula; Pires, Giovani De Lorenzi (Movimento, 2015)
This paper presents a portion of a doctoral thesis that uses case studies to investigate the curricular insertion of the ICTs in the education of teachers at three recently created universities in southern Brazil. The paper describes and analyzes the media-education experiences observed in the physical education course at Unipampa. The analysis of the proposals related to the ICTs was based on the three dimensions of media-education: instrumental, critical and expressive productive. The qualitative methodology used involves document analysis, interviews and direct observation for the production of data. The study found limited use of the ICTs in the curriculum studied, with an emphasis on the disciplinary approach.